TRoponin of Unknown origin in STroke evaluated by multi-component cardiac Magnetic resonance Imaging – The TRUST-MI study - Mengel, Annerose; Nenova, Lilyana; Müller, Karin A. L.; Poli, Sven; Kowarik, Markus C.; Feil, Katharina; Mizera, Lars; Geisler, Tobias; Kübler, Jens; Mahrholdt, Heiko; Ernemann, Ulrike; Hennersdorf, Florian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims Increased high-sensitive cardiac troponin I (hs-cTnI) levels are common in patients with acute ischemic stroke. However, only a minority demonstrates culprit lesions on coronary angiography, suggesting other mechanisms, e.g., inflammation, as underlying cause of myocardial damage. Late Gadolinium Enhancement (LGE)-cardiac magnetic resonance (CMR) with mapping techniques [T1, T2, extracellular volume (ECV)] allow the detection of both focal and diffuse myocardial abnormalities. We investigated the prevalence of culprit lesions by coronary angiography and myocardial tissue abnormalities by a comprehensive CMR protocol in troponin-positive stroke patients. Methods and results Patients with troponin-positive acute ischemic stroke and no history of coronary artery disease were prospectively enrolled. Coronary angiography and CMR (LGE, T1 + T2 mapping, ECV) were performed within the first days of the acute stroke. Twenty-five troponin-positive patients (mean age 62 years, 44% females) were included. 2 patients (8%) had culprit lesions on coronary angiography and underwent percutaneous coronary intervention. 13 patients (52%) demonstrated LGE: (i) n = 4 ischemic, (ii) n = 4 non-ischemic, and (iii) n = 5 ischemic AND non-ischemic. In the 12 LGE-negative patients, mapping revealed diffuse myocardial damage in additional 9 (75%) patients, with a high prevalence of increased T2 values. Conclusions Our data show a low prevalence of culprit lesions in troponin-positive stroke patients. However, > 50% of the patients demonstrated myocardial scars (ischemic + non-ischemic) by LGE-CMR. Mapping revealed additional myocardial abnormalities (mostly inflammatory) in the majority of LGE-negative patients. Therefore, a comprehensive CMR protocol gives important insights in the etiology of troponin which might have implications for the further work-up of troponin-positive stroke patients.